ANALISIS TUJUAN DAN FUNGSI HUKUM DALAM MEWUJUDKAN KETERTIBAN DAN KEADILAN SOSIAL - Hartono Hartono; Achmad Fahruddin; Ajis Supangat (Islamic Family Law, STAI Sangatta Kutai Timur, 2026)
Mahr constitutes a fundamental right of a wife and plays a significant role in marriage under Islamic law and Indonesian positive law. However, in practice, deviations continue to occur in the form of mahr fraud, particularly through the use of invalid financial instruments such as forged checks. This phenomenon raises legal issues concerning the validity of mahr, its implications for the marital relationship, and the protection of wives’ rights. This study employed a normative juridical method using statutory and conceptual approaches based on library research involving legislation, the Compilation of Islamic Law (KHI), and contemporary Islamic jurisprudence. The findings indicate that mahr in the form of a forged check does not fulfill the legal requirements of a valid mahr under Islamic jurisprudence and the KHI, as it lacks real economic value and cannot be validly transferred to the wife. Such a practice constitutes Ghurur Al-mahr (Mahr Fraud), which may undermine the wife's free and informed consent at the time of the marriage contract and has legal implications for the validity of the marriage, as regulated in Article 27 of Law Number 1 of 1974 on Marriage. In terms of legal protection, the wife is entitled to a substitute Mahr (Mahr Al-mithl) as a means of restoring her economic rights, in accordance with the principles of Maqasid Al-shari‘ah.